2023
DOI: 10.1002/tcr.202300247
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Perovskite‐Based Cathode Materials for Solid Oxide Fuel Cells: A Comprehensive Review

Ayesha Samreen,
Muhammad Sudais Ali,
Muhammad Huzaifa
et al.

Abstract: The high‐temperature solid oxide fuel cells (SOFCs) are the most efficient and green conversion technology for electricity generation from hydrogen‐based fuel as compared to conventional thermal power plants. Many efforts have been made to reduce the high operating temperature (>800 °C) to intermediate/low operating temperature (400 °C<T<800 °C) in SOFCs in order to extend their life span, thermal compatibility, cost‐effectiveness, and ease of fabrication. However, the major challenges in developing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 237 publications
0
1
0
Order By: Relevance
“…Iron-based perovskite oxides stand as widely investigated and cost-effective candidates for developing CO 2 -tolerant cathodes, including SrFeO 3− δ (SF), Bi x Sr 1− x FeO 3− δ , PrBaFe 2 O 5+ δ , and so on. 133–139 Yu et al demonstrated that the incorporation of U cations contributes to enhancing the structural stability of the SF oxide. As indicated by the XRD patterns in Fig.…”
Section: Strategies For Developing Co2-tolerant Perovskite Electrodesmentioning
confidence: 99%
“…Iron-based perovskite oxides stand as widely investigated and cost-effective candidates for developing CO 2 -tolerant cathodes, including SrFeO 3− δ (SF), Bi x Sr 1− x FeO 3− δ , PrBaFe 2 O 5+ δ , and so on. 133–139 Yu et al demonstrated that the incorporation of U cations contributes to enhancing the structural stability of the SF oxide. As indicated by the XRD patterns in Fig.…”
Section: Strategies For Developing Co2-tolerant Perovskite Electrodesmentioning
confidence: 99%